Parasitism and phenology of Dasineura mali (Diptera: Cecidomyiidae) in Canadian apple (Rosaceae) orchards. Issue 3 (7th June 2020) - Cossentine, J.E.; Brauner, A.M.; Franklin, J.L.; Robertson, M.C.; Buhl, P.N.; Blatt, S.; Gariepy, T.D.; Fraser, H.; Appleby, M.; Grigg-McGuffin, K.; Mason, P.G.
Abstract: The apple leaf midge, Dasineura mali (Kieffer) (Diptera: Cecidomyiidae), an invasive alien pest established for many years in Nova Scotia, Canada, has invaded Ontario and British Columbia, Canada apple ( Malus domestica Borkhausen; Rosaceae) orchards, damaging growing tips of trees. Molecular analysis indicated that Nova Scotia populations are genetically different from Ontario and British Columbia populations. Pheromone trap captures, oviposition on growing apple terminals, and the incidence of third instars indicate three D. mali generations in each province. Platygaster demades Walker (Hymenoptera: Platygastridae), released in Nova Scotia in 1993, parasitised 34% of the third midge generation in that province and was reared from D. mali for the first time in 2016 in the Fraser Valley of British Columbia. Lyrcus nigroaeneus Ashmead (Hymenoptera: Pteromalidae) parasitised up to 21% of D. mali in southwestern Ontario. Synopeas myles (Walker) (Hymenoptera: Platygastridae) was recorded from D. mali for the first time, one specimen in each of Nova Scotia and Ontario, and was the most important parasitoid in British Columbia. Synopeas myles parasitism in Okanagan and Similkameen, British Columbia orchards increased from 0% to a mean of 30% of D. mali larvae from 2014 to 2016. Other minor parasitoids included Platygaster tuberosula Kieffer (Hymenoptera: Platygasteridae) in all three provinces and Aphanogmus vicinus Förster (Hymenoptera: Ceraphronidae) in British Columbia.